APPLICATION OF RAW SECONDARY METABOLITES FROM TWO ISOLATES OF Trichoderma harzianum AGAINST ANTHRACNOSE ON RED CHILI PEPPER IN THE FIELD - Soesanto, Loekas; Mugiastuti, Endang; Suyanto, Agus; Rahayuniati, Ruth Feti (Universitas Lampung, 2020)
Anthracnose on red chili pepper is one of the highly damaging diseases that difficult to control bypesticides. This study aimed to determine the effect of raw secondary metabolites isolated from two isolates of Trichodermaharzianum towards anthracnose as well as the growth and yield of red chili pepper plants in the field. The research used arandomized block design with five treatments and seven replicates. The treatments tested were control, raw secondarymetabolites of T. harzianum T10 and T213, and their combination. The observed variables were incubation period, diseaseintensity, the late population density of T. harzianum, plant height, root length, fresh and dry weight of the plant and root,flowering time, number of fruits per plant, fresh weight of fruit, and phenolic compound content analysis. The result showedthat the raw secondary metabolites from the combination of the two T. harzianum isolates were the best treatments that couldlengthen the incubation period and decrease the disease intensity as 30.2 and 87.05%, respectively. However, these applicationscould not increase the growth components; while for the yield components, the application could improve the number of fruitsper plant and fresh weight of fruit as 15.33 and 34.53%, respectively.